Effect of intercropping on the Cd accumulation in soil and rice plants: A review - Sajjad Shaker; Mohammad Rabiee (Muhandisī-i Bihdāsht-i Muḥīṭ)
Background: A high cadmium (Cd) concentration in the paddy soil and translocation to the rice grain and the food chain is a serious environmental problem. Hence, it is essential to develop strategies for reducing Cd accumulation in rice and maintaining food safety. Phytoremediation is a cost-effective technique used to extract or remove Cd from contaminated sites. Intercropping is regarded as an effective technique for enhancing the Cd phytoremediation efficiency. According to this, the purpose of this study was to evaluate the effect of intercropping on the Cd accumulation in soil and rice plants. Methods: Data for the present study was collected through searching articles in databases, including Google Scholar, Springer, ScienceDirect, ProQuest, PubMed, ResearchGate, Scopus and Elsevier. In the initial search, a total of 62 articles were found in the period 2003 to 2022, and was reduced after removing duplicates to 45 articles. Then, in the screening stage, the title and abstract of the articles were reviewed and at the end, 29 articles remained. The full text of the screened articles was studied and finally, 19 articles were used in this study. Results: The results showed that intercropping of the high-Cd and the low-Cd rice cultivars is an advantageous practice for Cd remediation in paddy soils. So that intercropping with the high-Cd rice cultivar decreased grain Cd content, and improved the yield of the low-Cd rice cultivar. Also, intercropping of rice with Water spinach, Sesbania cannabina, Alligator flag, Sphagneticola calendulacea, Canna indica and Pontederia cordata, can function as an effective way for Cd remediation and guarantee rice grain safety. Conclusion: Intercropping with hyperaccumulator plants is ideal to achieve safe rice production and phytoremediation of Cd-contaminated soil.